2009
DOI: 10.1103/physrevlett.102.136104
|View full text |Cite
|
Sign up to set email alerts
|

Magic-Sized Diamond Nanocrystals

Abstract: The 2D structural transformation of a heavily boron-doped diamond surface has been revealed using scanning tunneling microscopy (STM). We found that at boron densities above the metal-insulator transition the diamond surface is comprised of spatially ordered magic-sized nanocrystals. The development of quantized electron gas inside these nanocrystals is directly confirmed by STM observation of standing electron waves. The experimental comparison of metallic and insulating diamond reveals the existence of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The ⌬ nanomodulation observed in sample s3 is in agreement with the rencent results reported by Altfeder et al, 13 who studied the surfaces of boron-doped diamond films by performing STM experiments. It has been found that these surfaces reveal spatially ordered magic-sized nanocrystals by showing an arrangement of the LDOS in parallelograms with base and height sizes equal to 8.3 and 10.5 nm, respectively.…”
Section: Intrinsic Granularitysupporting
confidence: 91%
See 2 more Smart Citations
“…The ⌬ nanomodulation observed in sample s3 is in agreement with the rencent results reported by Altfeder et al, 13 who studied the surfaces of boron-doped diamond films by performing STM experiments. It has been found that these surfaces reveal spatially ordered magic-sized nanocrystals by showing an arrangement of the LDOS in parallelograms with base and height sizes equal to 8.3 and 10.5 nm, respectively.…”
Section: Intrinsic Granularitysupporting
confidence: 91%
“…It will be shown that our results are in agreement with the recent observation of modulated local density of states ͑LDOS͒ on surfaces of boron-doped diamond films. 13 On the other hand, the superconducting gap ⌬, extracted from the I-V curves measured at a fixed point and at different temperatures, shows its temperature dependence ͓⌬͑T͔͒ different from that predicted by the BCS theory. The ⌬͑T͒ is significantly affected between 2 and 1 K, below which it saturates.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most of the junctions were found to be more transparent as can be seen following a line between positions 4 and 5 with progressive variations in the gray scale reminiscent of the superconducting proximity effect. We did not observe any quantum confinement effect 22 within a grain, presumably because of the strong intergrain coupling in our samples. Our results are in strong contrast with a recent STM study on one polycrystalline diamond film, where a strong and short-range modulation of the superconductivity was observed within the same grain.…”
Section: Fig 2 ͑Color Online͒ ͑A͒ Two-dimensional View Ofmentioning
confidence: 52%
“…On the other hand, diamond is an ideal candidate for electronic devices because of its extreme properties like high thermal conductivity, high mechanical strength, and optical transparency. 5,6 These extreme properties of diamond film have triggered many studies on diamond including its application in electronic devices under extreme operating conditions, where Si-, Ga-, and As-based devices are not suitable.…”
Section: Introductionmentioning
confidence: 99%